2023
DOI: 10.1002/wps.21034
|View full text |Cite
|
Sign up to set email alerts
|

New insights from the last decade of research in psychiatric genetics: discoveries, challenges and clinical implications

Abstract: Psychiatric genetics has made substantial progress in the last decade, providing new insights into the genetic etiology of psychiatric disorders, and paving the way for precision psychiatry, in which individual genetic profiles may be used to personalize risk assessment and inform clinical decision‐making. Long recognized to be heritable, recent evidence shows that psychiatric disorders are influenced by thousands of genetic variants acting together. Most of these variants are commonly occurring, meaning that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 358 publications
(531 reference statements)
3
57
0
Order By: Relevance
“…The authors of this study found a total of 10 genes to be commonly associated with the risk of OCD, schizophrenia, bipolar disorder, and autism spectrum disorder. Altogether, these findings might suggest that cross-disorder genetic backgrounds may underlie shared correlates within a higher-order structure of psychopathology [55].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this study found a total of 10 genes to be commonly associated with the risk of OCD, schizophrenia, bipolar disorder, and autism spectrum disorder. Altogether, these findings might suggest that cross-disorder genetic backgrounds may underlie shared correlates within a higher-order structure of psychopathology [55].…”
Section: Discussionmentioning
confidence: 99%
“…Most psychiatric disorders have a high heritability, with estimates between 40% and 80% [50], and are highly polygenic [51]. Lately, there has been a large increase in discoveries of genetic variants associated with psychiatric disorders [50], followed by the development of PRS-based tools [51]. However, PRS for psychiatric disorders explain relatively small proportions of the liability of each disorder, and the current PRS are still not clinically useful [52].…”
Section: Precision Medicine In Psychiatrymentioning
confidence: 99%
“…In recent years, the study of genetic risk factors has received increasing attention in the study of inter-individual differences in mental health (Andreassen, Hindley, Frei, & Smeland, 2023). Twin and family studies aim to estimate the influence of genetic and environmental influences on the variation of traits or disorder risk using the information on genetic relatedness and shared family environment (Shih, Belmonte, & Zandi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For psychiatric symptoms and disorders, the so called SNP-based heritability, i.e. the variance explained by the common variants assessed in a GWAS, usually accounts for around one third of the heritabilities estimated in twin studies (Andreassen et al, 2023). Besides insights into specific genes and pathways involved in disease etiology, GWAS also allow the estimation to what degree the association signal, and thereby the underlying genetic factors, are shared between disorders and traits.…”
Section: Introductionmentioning
confidence: 99%